The Legal Validity of the Sale and Purchase Deed Executed Before the Land Deed Official Pursuant to a Power of Attorney in the Notarial Sale and Purchase Agreement - Alatas, Husein; Sihotang, Sudiman; Ilyanawati, R. Yuniar Anisa; Yusuf, Muhammad Arsjad (DE'RECHTSSTAAT, 2025)
The purpose of this research is to analyze the position of the authentic deed in the evidence in the trial of civil cases and to find out and analyze the legal force of the sale and purchase deed before the official who made the land deed made based on the power of attorney stated in the deed of the notary sale and purchase binding agreement. This research method uses a normative juridical approach that emphasizes literature studies with the addition of literature, namely decision studies to strengthen the analysis and produce accurate conclusions. The results of the study show that first, the power of attorney listed in the PPJB deed is a unit that is not separate from the PPJB deed as an authentic deed and becomes full proof for judges in civil trials. Second, that the AJB made before PPAT based on the power of attorney stated in the PPJB Notarial deed has perfect legal force and is legally binding and the power of attorney listed in the notary deed is valid as authentic evidence.